Open Versus Laparoscopic Appendicectomy in Pediatric Patients; A Comparative Study in A Single Center: Open and Laparoscopic Appendicectomy in Pediatric Patients - Rehman, Hayat Ur; Naeem, Tahir; Bugti, Quratulain; Shah, Vaqar-E-Sahar; Fayaz, Muhammad; Rashid, Muhammad (Pakistan Journal of Health Sciences, 2022)
Appendicitis is the commonest surgical emergency in paeadtric patients. Appendicectomy is still being performed by both open and laparoscopic methods. The first laparoscopic appendicectomy was performed in 1983. Objective: To compare the outcome of open appendectomies with laparoscopic appendectomies in pediatric patients was the objective of this study. Methods: Two hundred pediatric patients of both genders with acute appendicitis were enrolled from emergency department of Pediatric Surgery, Qazi Hussain Ahmad medical complex, Nowshehra, from March 2020- December 2020. In this convenient study patients were dividing into two groups. Group A patients received open appendectomy and Group B received laparoscopic appendectomy. Outcome of both procedures were noted and compared between groups by chi square test. Results: Mean ages of patients were 10.11±2.67 and 10.01±2.31 years (p=0.796) in group A and B, respectively. There were 63.0% and 69.0% males 1) in group A and B, respectively. Mean operative time, mean hospital stay and mean VAS were26.19±8.14 vs. 36.79±11.41 min.,2.01±0.61 vs. 1.03±0.01 days and 3.67±1.41 and 6.07±2.01 (p=0.000) in group A and B, respectively. Complications were hemorrhage (0.0% vs. 0.0%; p=1.0), Iatrogenic injury (0.0% vs. 0.0%; p=1.0) and Pelvic collection (3.0% vs. 0.05; p=1.0), SSI (6.0% vs. 0.0%; p=0.00) in group A and B, respectively. None of the pediatric patients after laparoscopic appendectomy required another exploration to deal with complications however, 3.0% patients needed exploration in open appendectomy. No mortality (0.0%) was observed in any group. Conclusions: laparoscopic appendectomies in pediatric patients is safe and feasible as compared to open appendectomy